Management of cervical cancer in pregnancy in a low resource setting: a rare case report - Namkha Dorji; Rojna Rai; Nishal Chhetri; Sangay Tshering; Sonam Dechen (BMC, 2024)
Abstract Background Cervical cancer in pregnancy is a rare event. Diagnosis and management of cervical cancer in pregnancy is complicated and challenging in a low resource setting. Case presentation Herein, we present a case of cervical cancer (FIGO stage IB3) diagnosed at 28+ 5 weeks and successfully managed at 37+ 2 weeks of gestation in a 27-year-old woman. Conclusion This is the first case report on cervical cancer in pregnancy from Bhutan. It highlights the diagnostic and management challenges in a low resource country.